Cancer information overload and multiple prevention behaviors. (30th September 2020) - Breyton, M; Smith, A B; Rouquette, A; Mancini, J
Abstract: Background: Many people feel overwhelmed by the increasing amount of cancer-related material available in the information environment. Our aims was to evaluate the psychometric properties of the brief version of the cancer information overload (CIO) scale and to examine the association between CIO and multiple cancer prevention behaviors. Methods: A large survey using a self-administered online questionnaire was proposed to all adult members of the Seintinelles, a French national non-profit organization. The psychometric properties of the CIO scale were evaluated. Measurement invariance across French and English languages was studied using an additional sample of 224 Australian cancer survivors from Register4. We also collected functional, communicative, and critical health literacy (FCCHL), deprivation (EPICES index), current smoking, alcohol misuse, frequent sunburns, and rare skin self-examination. Results: Between June 16th and 30th 2016, 2 363 French participants answered the online questionnaire. The five-item CIO scale demonstrated the best balance between psychometric properties and number of items. It showed satisfactory internal consistency and adequate fit. No measurement invariance issue was found across age, gender, education level, and language groups. CIO was increased among people with higher deprivation, lower education and a cancer information avoidant profile. In multivariate analyses, CIO was associated with tobacco use (OR = 1.05, 95%CI [1.00-1.10]), rare skin checks (OR = 1.05 [1.01-1.08]) and frequent sunburns (OR = 1.04 [1.01-1.07]), but not with alcohol misuse. Conclusions: The 5-item CIO scale is ready to be used in French and English-speaking countries. The links observed between CIO and multiple prevention behaviors encourage further research in order to better characterize the psycho-cognitive and environmental phenomena at play. Efforts are needed to communicate adequately and empower citizens to limit the growing burden of cancer. Key messages: The 5-item CIO scale is ready to be used in French and English-speaking countries. Efforts are needed to communicate adequately and empower citizens to limit the growing burden of cancer.